Isolation and characterization of the mitochondrial genome of Gymnodraco acuticeps (Perciformes: Bathydraconidae) with phylogenetic consideration - Wei Song; Lingzhi Li; Hongliang Huang; Fenfang Chen; Ming Zhao; Keji Jiang; Fengying Zhang; Chunyan Ma; Xuezhong Chen; Lingbo Ma (Mitochondrial DNA. Part B. Resources, 2017)
Gymnodraco acuticepsis is an Antarctic fish living in the Southern Ocean. Until now, studies on G. acuticeps are still limited. As an Antarctic fish, obtaining and characterization of the mitochondrial genome of G. acuticeps will be important for elucidation of the mechanism of cold-adapting evolution in mitochondrion. In this study, we first isolated and characterized the mitochondrial genome sequence of G. acuticeps with 15,987 bp in length. It contained of 34 genes (12 protein-coding genes, 20 transfer RNA genes, 2 ribosomal RNA genes) and a partial putative control region. Gene organization and nucleotide composition of obtained mito-genome were similar to those of other Antarctic fish. Twenty-eight genes were encoded by heavy strand, while six genes were encoded by light strand. Further, the phylogenetic tree, which based on 12 protein-coding genes, revealed that the G. acuticeps was genetically closest to species Parachaenichthys charcoti among 18 species. We hope this work would be helpful for the population genetics and molecular evolution studies.